Improving the photovoltaic performance of co‐evaporated Cu2ZnSnS4 thin‐film solar cells by incorporation of sodium from NaF layers. (22nd January 2016) - Mise, Takahiro; Tajima, Shin; Fukano, Tatsuo; Higuchi, Kazuo; Washio, Tsukasa; Jimbo, Kazuo; Katagiri, Hironori
Abstract: We have investigated the influence of sodium (Na) on the properties of co‐evaporated Cu2 ZnSnS4 (CZTS) layer microstructures and solar cells. The photovoltaic performance and diode properties were improved by incorporating Na from NaF layers into the CZTS layers, while Na had a negligible effect on the microstructural properties of the layer. The best cell fabricated by using an optimal CZTS layer (Cu/(Zn + Sn) = 0.70, Zn/Sn = 1.8) yielded an active area efficiency of 5.23%. The analysis of device properties suggests that charge‐carrier recombination at CZTS/CdS interface is suppressed by intentional Na incorporation from NaF layers. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : We demonstrated vacuum‐based co‐evaporation without atmospheric sulfurization as a one‐step process for direct deposition of Cu2 ZnSnS4 layers and investigated the influence of sodium incorporation from NaF layers on the layer microstructure and solar cell properties. The best cell using 40‐nm‐thick NaF yielded active area efficiency of 5.23% ( V oc  = 603 mV, J sc  = 13.0 mA/cm 2, and FF = 0.668). The device properties were evaluated to elucidate the charge‐carrier recombination mechanism of co‐evaporated Cu2 ZnSnS4 cells.